Use of BIM with photogrammetry support in small construction projects. Case study for commercial franchises - Loredo Conde, Antonio J.; García-Sanz-Calcedo, Justo; Reyes Rodríguez, Antonio M. (Journal of Civil Engineering and Management, 2020)
Building Information Modelling for small constructions is a useful working tool aimed at providing alternative solutions in building engineering. However, it is not commonly applied to this purpose, and even less together with photogrammetry techniques. This work seeks to analyse the advantages of this methodology with photogrammetry support in small projects. To this end, 121 commercial franchise projects in the field of perfume and cosmetic industry were studied in order to assess the benefits of BIM methodology. These projects were developed between 2011 and 2016. BIM protocols were shown to achieve 20% reduction in costs per project and in working periods (4.11 days), which led to a productivity improvement exceeding 27%. The total period until opening to public was observed to decrease in 10.09 days, and the number of inquiries and doubts during the project execution phase handled by the construction companies were seen to reduce by 25%. Moreover, the return of investment (ROI) corresponding to the implementation of BIM protocols was found to be more favourable than that of CAD (41.88%), with associated internal rate of return (IRR) of 34.5%. The validity of the results is limited to the scope of works for small commercial premises.